Ostracode biofacies and shell chemistry reveal quaternary aquatic transitions in the Pozuelos basin (Argentina) - McGlue, Michael M. (2017)
Here we present the ﬁrst use of calcareous microfossils to examine the late Quaternary paleoecology of the endorheic Pozuelos Basin (Argentina). Modern deposition in the basin centers on Laguna de los Pozuelos (LP),a shallow playa-lake that is fed by axial rivers and groundwater and dominantly accumulates siliciclastic sediments.Today, the distribution of limnocytherid and cypridoidean ostracodes across southern LP is strongly inﬂuenced bydistance to the Rıo Cincel delta, whereas the northern end of the playa-lake is characterized by a paucity of ostracodes due to frequent sub-aerial exposure. Ten ostracode biofacies deﬁne a sediment core retrieved from LP,which reveal progressive changes in aquatic environments that varied in salinity, depth, and proximity to deltas over the late Pleistocene. Closed lakes occupied the basin from ~ 37.6?30.7 ka, ~ 28.0?25.0 ka, and ~ 23.0?16.6 ka,whereas saline wetlands occurred when these lakes contracted. Extant LP has no analog in the late Pleistocene record; it formed after ~ 7.2 ka, following a hiatus that removed the Pleistocene?Holocene transition.Paleoecological evidence indicates that the core site was inﬂuenced by deltaic inﬂows from the eastern basin margin until ~ 24.3 ka, an area where today dry alluvial fans are found. Reorganization of the watershed by normalfaulting, most likely at ~ 18.0 ka, appears to have reduced the inﬂuence of these deltaic inﬂows. Extensional neotectonics, perhaps induced by incorporation of the Pozuelos Basin into the Andean hinterland, is a mechanism that along with tropical climate change is potentially important to water balance and ecology in high-altitude convergent orogenic basins.